VOCATIONAL GUIDANCE AND CAREER MATURITY AMONG SECONDARY SCHOOL STUDENTS: AN INDIAN EXPERIENCE - Sirohi, Vineeta (European Scientific Journal, ESJ, 2013)
This study is focused on the stage of secondary education which is a critical period for the development of career maturity, when students are faced with ongoing academic and occupational decisions over the course of their study and these educational and vocational decisions pave the way for future decisions to be taken by any individual in the world of work. The present study aimed to examine the career maturity of secondary school students, by gender, type of school and vocational guidance provisions and know the perception of students about vocational guidance services in their schools. A sample of 160 students was drawn from eight secondary schools through stratified sampling technique. The quantitative and qualitative analysis of data revealed that females are found to possess higher career maturity than their male counterparts. Students of private schools show higher career maturity attitude as compared of students of government schools. Moreover, students in schools with vocational guidance and counseling provisions show high career maturity in self awareness and occupational information as compared to none from those schools which are deprived of these provisions, similarly in choosing a job, the students who are privileged to be exposed to the guidance and counseling programmes show much higher career maturity than their underprivileged counterpart. The findings of the study have strong implications for the policy makers and educationists for institutionalizing the vocational guidance and counseling programmes in secondary schools and delivering planned and systematic counseling interventions to increase the career maturity of secondary school students.